Positive electrode and lithium secondary battery including same
By adopting a multi-layer structure in the positive electrode, using the combination of lithium iron phosphate, conductive material and adhesive, the adhesion between the positive electrode current collector and the active material layer is improved, the problem of insufficient adhesion of the positive electrode is solved, and the battery capacity is achieved and the improvement of output characteristics.
Patent Information
- Application Number
- CN202380051661.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-16
- Filing Date
- 2023-12-15
- Publication Date
- 2025-02-18
AI Technical Summary
In the positive electrode containing lithium iron phosphate, the adhesion between the positive electrode current collector and the positive electrode active material layer is insufficient, resulting in an increase in battery resistance and a decrease in capacity, especially under high load conditions.
The positive electrode adopts a multi-layer structure, wherein the first positive electrode active material layer and the second positive electrode active material layer each include lithium iron phosphate, a conductive material, a fluorine-based adhesive, a rubber-based adhesive, and a rubber-based dispersant, and the second The weight ratio of fluorine in the cathode active material layer is small, and the weight of the first cathode active material layer is in the range of 17% to 99% of the total weight.
By improving the adhesion of the positive electrode, preventing electrode dissociation, reducing battery resistance, and improving the capacity and output characteristics of the lithium secondary battery.
Smart Images

Figure BDA0005226581330000241 
Figure BDA0005226581330000251 
Figure BDA0005226581330000271
Abstract
Description
Technical Field
[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0177477, filed on December 16, 2022, the disclosure of which is incorporated herein by reference in its entirety.
[0002] The present disclosure relates to a positive electrode and a lithium secondary battery manufactured using the positive electrode. Background Art
[0003] As the technology of electric vehicles and energy storage systems (ESS) develops and the demand increases, the demand for batteries as energy sources is rapidly increasing, and therefore, various studies have been conducted on batteries that can meet various needs. In particular, lithium secondary batteries with high energy density and excellent life and cycle characteristics have been actively studied as power sources for such devices.
[0004] As a positive electrode active material of a lithium secondary battery, lithium cobalt oxide (LCO), lithium nickel cobalt manganese oxide (LNCMO), lithium iron phosphate (LFP), and the like have been used.
[0005] Lithium iron phosphate is inexpensive because it is abundant in resources and includes iron as a low-cost material. In addition, since lithium iron phosphate has low toxicity, environmental pollution can be reduced when lithium iron phosphate is used. In addition, since lithium iron phosphate has an olivine structure, the active material structure can be stably maintained at high temperatures compared to lithium transition metal oxides having a layered structure. Therefore, it has the advantages of excellent high temperature stability and high temperature life characteristics of the battery.
[0006] However, lithium iron phosphate has problems of low lithium mobility and low conductivity compared to lithium transition metal oxides such as lithium nickel cobalt manganese oxide. Therefore, lithium iron phosphate with a smaller average particle size is used to form a short lithium movement path, the surface of lithium iron phosphate is coated with carbon to improve conductivity, and an excess of conductive material is used.
[0007] However, as the size of lithium iron phosphate particles decreases, the specific surface area increases, and lithium iron phosphate with a carbon-coated surface has low solvent wettability. As a result, lithium iron phosphate particles are severely agglomerated, which reduces the stability and coating processability of the positive electrode slurry, and effective mixing of lithium iron phosphate and a binder is impossible, which reduces the adhesion between the positive electrode current collector and the positive electrode active material layer in the prepared positive electrode (hereinafter referred to as positive electrode adhesion). This phenomenon may be more aggravated in a highly loaded positive electrode.
[0008] Low cathode adhesion may cause dissociation of the cathode active material layer during electrode manufacturing or during charge and discharge, resulting in increased battery resistance and decreased capacity of the secondary battery.
[0009] As the demand for high energy density batteries continues to increase, technologies are needed to improve cathode adhesion in cathodes containing lithium iron phosphate while achieving 550 mg / 25 cm 2 or higher loads. Summary of the invention
[0010] Technical issues
[0011] The present invention aims to solve the above-mentioned problems and aims to provide adhesion between a cathode current collector and a cathode active material layer in a high-load cathode, and a lithium secondary battery manufactured using the adhesion, in which electrode dissociation is prevented by improving flexibility.
[0012] Technical Solution
[0013] According to one embodiment of the present invention, a positive electrode is provided. The positive electrode includes: a positive electrode collector; a first positive electrode active material layer, the first positive electrode active material layer is formed on one side or both sides of the positive electrode collector; and a second positive electrode active material layer, the second positive electrode active material layer is formed on the first positive electrode active material layer; wherein the first positive electrode active layer and the second positive electrode active layer each include lithium iron phosphate, a coating material, a fluorine-based adhesive, a rubber-based adhesive, and a rubber-based dispersant, and the weight P2 of fluorine contained in the second positive electrode active layer and the weight P1 of fluorine contained in the first positive electrode active layer (P2 / P1) is 1 or less, and the weight (A) of the first positive electrode active layer is in the range of 17% to 99% of the total weight (A+B) of the first positive electrode active layer and the second positive electrode active layer.
[0014] In exemplary embodiments, the weight of the first positive active material layer (A) may be in the range of 20% to 85% of the total weight (A+B) of the first positive active material layer and the second positive active material layer.
[0015] In exemplary embodiments, the rubber-based adhesive and the rubber-based dispersant may be hydrogenated nitrile rubber (HNBR), respectively.
[0016] In an exemplary embodiment, the rubber-based adhesive may be hydrogenated nitrile rubber (HNBR) having a weight average molecular weight (Mw) of at least 130,000 g / mol, preferably in a range of 150,000 g / mol to 1,000,000 g / mol.
[0017] In exemplary embodiments, the rubber-based dispersant may be hydrogenated nitrile rubber (HNBR) having a weight average molecular weight (Mw) in the range of 10,000 g / mol to 100,000 g / mol.
[0018] In an exemplary embodiment, the lithium iron phosphate included in the first positive active material layer may include an average particle size D 50 The first lithium iron phosphate has an average particle size D of 0.5 μm to 2 μm. 50 The second lithium iron phosphate has a thickness of 3.5 μm to 15 μm.
[0019] In this case, a weight ratio of the first lithium iron phosphate to the second lithium iron phosphate may be 50:50 to 99.9:0.1.
[0020] In an exemplary embodiment, the average particle size D of the lithium iron phosphate included in the second positive electrode active material layer is 50 It can be 0.6 μm to 3.0 μm.
[0021] In exemplary embodiments, the lithium iron phosphate may be a compound represented by Formula 1 below.
[0022] [Formula 1].
[0023] Li 1+a Fe 1-x M x (PO 4-b )X b
[0024] (In the above formula 1, M includes one or more elements selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, X includes one or more elements selected from the group consisting of F, S, and N, and a, b, and x are -0.5≤a≤0.5, 0≤b≤0.1, and 0≤x≤0.5, respectively.)
[0025] In exemplary embodiments, the fluorine-based binder may be included in the first positive active material layer in an amount of 1.5 wt % to 3.0 wt %.
[0026] In exemplary embodiments, the fluorine-based binder may be included in the second positive active material layer in an amount of 0.8 wt % to 2.4 wt %.
[0027] In exemplary embodiments, the fluorine-based adhesive may be a polyvinylidene fluoride (PVdF)-based polymer adhesive.
[0028] In exemplary embodiments, the rubber-based binder included in each of the first positive electrode active material layer and the second positive electrode active material layer may satisfy the following Condition 1.
[0029] [Condition 1].
[0030] 1≤R2 / R1≤3
[0031] R1 represents the content (wt%) of the rubber-based binder in the first positive electrode active material layer,
[0032] R2 represents the content (wt%) of the rubber-based binder in the second positive electrode active material layer.
[0033] In exemplary embodiments, the rubber-based binder may be included in an amount of 0.2 wt % to 0.9 wt % in the first positive active material layer, and in an amount of 0.3 wt % to 1.0 wt % in the second positive active material layer.
[0034] In an exemplary embodiment, the conductive material may be carbon nanotubes.
[0035] In exemplary embodiments, the conductive material may be included in each of the first and second positive electrode active material layers in an amount of 0.3 wt % to 2.0 wt %.
[0036] The present disclosure also provides a lithium secondary battery including the positive electrode described above.
[0037] Beneficial Effects
[0038] Since the positive electrode according to the present invention includes the first positive active material layer maximizing adhesion and the second positive active material layer contributing to improved flexibility, the positive electrode can have excellent adhesion and flexibility with a low content of binder compared to a conventional single-layer positive electrode.
[0039] In addition, the positive electrode according to the present invention has excellent adhesion by controlling the weight ratio of the first positive electrode active material layer and the second positive electrode active material layer within an appropriate range. DETAILED DESCRIPTION
[0040] Hereinafter, the present invention will be described in more detail to provide a better understanding of the present invention.
[0041] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings. Prior to this, the terms and words used in this specification and claims should not be interpreted as limited to general terms or dictionary terms, but should be interpreted based on the concept that the inventor has properly defined the terms in order to best explain the principles of the present invention, the meaning and concept of the technical ideas according to the present invention.
[0042] The terms used in this specification are only used to describe exemplary embodiments and are not intended to limit the present invention. Unless the context clearly indicates otherwise, expressions in the singular form also include the plural form.
[0043] The terms "include", "comprising" and "having" used in this document indicate the existence or combination of the features, quantities, steps, actions, components, or members described in the specification, and it should be understood that the possibility of the existence or addition of one or more other features, quantities, steps, actions, components, members, or combinations thereof is not precluded.
[0044] In the present specification, "%" means weight % unless otherwise specifically stated.
[0045] In this specification, the average particle size D 50 The average particle size D can be defined as the particle size at 50% of the particle size distribution and can be measured using a laser diffraction method. 50 It can be calculated by dispersing the target particles in a dispersant, introducing them into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), irradiating them with ultrasonic waves of about 28 kHz at a power of 60 W, and then calculating the average particle diameter D at 50% of the cumulative distribution of the particle volume based on the particle diameter in the measuring device. 50 .
[0046] In this specification, the "specific surface area" is measured by the Brunauer-Emmet-Teller (BET) method, and can be specifically calculated from the amount of nitrogen gas adsorbed at liquid nitrogen temperature (77K) using BELSORP mini II commercially available from BEL Japan.
[0047] In this manual, “ ” refers to the diameter of the measuring rod in millimeters (mm).
[0048] In this specification, "weight average molecular weight (Mw)" refers to a conversion value relative to standard polystyrene measured by gel permeation chromatography (GPC). Specifically, the weight average molecular weight is a value obtained by converting a value measured under the following conditions using GPC, and a calibration curve is prepared using standard polystyrene of Agilent system.
[0049] <Measurement conditions>
[0050] Measuring instrument: Agilent GPC (Agilent 1200 series, USA)
[0051] Column: Connect two PL Mixed B
[0052] Column temperature: 40°C
[0053] Eluent: Tetrahydrofuran
[0054] Flow rate: 1.0mL / min
[0055] Concentration: ~1 mg / mL (100 μL injection)
[0056] In this specification, positive electrode adhesion can be measured as follows. A positive electrode cut into a size with a length of 150 mm and a width of 20 mm is prepared, and it is attached to a slide glass with a length of 75 mm and a width of 25 mm in the length direction using a double-sided tape so that the positive electrode active material layer faces the slide glass. That is, the slide glass is attached to an area corresponding to half of the length direction of the positive electrode. Afterwards, a roller is used to rub 10 times so that the double-sided tape is evenly attached, thereby preparing an evaluation sample. Next, the slide glass portion of the evaluation sample is fixed to the sample stage of a universal testing machine (Universal Testing Machine, UTM) (LS5, AMETEK), and half of the positive electrode to which the slide glass is not attached is connected to the load sensor of the UTM. While the load sensor is moved to 50 mm at an angle of 90 ° and a speed of 100 mm / min by force, the load applied to the load sensor is measured. In this case, the average value of the load measured in a segment of 20 mm to 40 mm during the driving segment can be obtained. This procedure was repeated 5 times in total, and the average value was evaluated as the positive electrode adhesion (gf / 20 mm) of each sample.
[0057] The present invention provides a positive electrode and a lithium secondary battery manufactured using the positive electrode.
[0058] Generally, lithium iron phosphate used as a positive electrode active material has low lithium mobility and low conductivity compared to lithium transition metal oxides such as lithium nickel cobalt manganese oxide, so lithium iron phosphate with a smaller average particle size is generally used as a positive electrode active material. However, the small size of lithium iron phosphate particles increases the specific surface area, which may lead to severe particle agglomeration, which hinders the effective mixing of lithium iron phosphate and the binder, resulting in reduced positive electrode adhesion. In addition, the fluorine-based binder used as a positive electrode binder is characterized in that its adhesion to lithium iron phosphate particles is better than its adhesion to the positive electrode collector, so that when the positive electrode active material is lithium iron phosphate, the interface adhesion between the positive electrode collector and the positive electrode active material layer is reduced compared to when the positive electrode active material is lithium nickel cobalt manganese oxide. Therefore, the positive electrode including lithium iron phosphate as the positive electrode active material has the problem of dissociation of the positive electrode active material layer during electrode manufacturing or charging and discharging, resulting in an increase in the resistance of the battery and a decrease in the capacity of the secondary battery. Furthermore, compared with a positive electrode including lithium nickel cobalt manganese oxide as a positive electrode active material, a positive electrode including lithium iron phosphate has poor brittleness due to characteristics of the positive electrode active material, and the positive electrode active material layer is easily dissociated due to physical external force.
[0059] Therefore, the inventors of the present invention have conducted research to solve these problems, and have found that the positive electrode active material layer is composed of a multilayer rather than a single layer, wherein the first positive electrode active material layer and the second positive electrode active material layer each contain lithium iron phosphate, a conductive material, a fluorine-based adhesive, a rubber-based adhesive, and a rubber-based dispersant, and the ratio (P2 / P1) of the weight P2 of fluorine contained in the second positive electrode active material layer to the weight P1 of fluorine contained in the first positive electrode active material layer is 1 or less, wherein the weight (A) of the first positive electrode active material layer is in the range of 17% to 99% of the total weight (A+B) of the first positive electrode active material layer and the second positive electrode active material layer, and the interface adhesion between the collector and the first positive electrode active material layer is excellent, and at the same time, the dissociation of the positive electrode active material layer is suppressed due to the improved flexibility, thereby making the present invention.
[0060] The positive electrode according to an exemplary embodiment of the present invention is a structure in which the positive electrode active material layer is in direct contact with the positive electrode current collector, and due to the excellent interfacial adhesion between the positive electrode active material layer and the positive electrode current collector, the positive electrode active material may not include a separate layer for improving the adhesion between the positive electrode active material layer and the positive electrode current collector. In other words, the positive electrode according to an embodiment of the present invention may exhibit excellent interfacial adhesion between the positive electrode active material layer and the positive electrode current collector without including a separate layer that may be interposed to improve adhesion, such as an adhesion layer or a bonding layer or a bonding layer or a primer coating.
[0061] The positive electrode of the present invention will be described in detail.
[0062] A positive electrode according to one embodiment of the present invention may include a positive electrode active material layer. Specifically, a positive electrode according to the present invention may include a positive electrode current collector; a first positive electrode active material layer formed on the current collector; and a second positive electrode active material layer formed on the first positive electrode active material layer. The first positive electrode active material layer and the second positive electrode active material layer may be formed on one side or both sides of the current collector.
[0063] In an exemplary embodiment of the present invention, the weight (A) of the first positive electrode active material layer may be in the range of 17% to 99%, preferably 20% to 85%, and more preferably 25% to 75% of the total weight (A+B) of the first positive electrode active material layer and the second positive electrode active material layer. When the weight (A) of the first positive electrode active material layer accounts for the above range, it may have the required adhesion to the positive electrode while exhibiting sufficient flexibility to prevent the positive electrode active material layer from being desorbed due to physical external force.
[0064] The positive electrode current collector is not particularly limited as long as it does not cause chemical changes in the battery and has electrical conductivity. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, etc. can be used as the current collector.
[0065] The positive electrode current collector may have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on its surface to increase adhesion to the positive electrode active material layer. For example, the positive electrode current collector may be used in various forms such as films, sheets, foils, nets, porous bodies, foams, nonwoven fabrics, and the like.
[0066] The first positive electrode active material layer and the second positive electrode active material layer may include positive electrode active materials, respectively. In addition, as needed, the first positive electrode active material layer and the second positive electrode active material layer may further include a conductive material, a binder, and a dispersant in addition to the positive electrode active material.
[0067] Hereinafter, each component included in the first positive electrode active material layer and the second positive electrode active material layer will be described in detail.
[0068] (1) Positive electrode active material
[0069] The present disclosure includes a lithium transition metal phosphate as a positive electrode active material. The lithium transition metal phosphate has an olivine structure, so the active material structure remains stable at high temperatures compared to a lithium transition metal oxide having a layered structure. As a result, when a lithium transition metal phosphate is used as a positive electrode active material, the high temperature stability and high temperature life characteristics of the positive electrode are significantly improved, so that the risk of ignition of a lithium secondary battery including the positive electrode can be reduced.
[0070] The lithium iron phosphate may be a compound of Formula 1 below.
[0071] [Formula 1]
[0072] Li 1+a Fe 1-x M x (PO 4-b )X b
[0073] In Formula 1, M includes any one or more elements selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, X includes any one or more elements selected from the group consisting of F, S, and N, and a, b, and x are -0.5≤a≤0.5, 0≤b≤0.1, and 0≤x≤0.5, respectively.
[0074] For example, the lithium iron phosphate may be LiFePO4.
[0075] In the present disclosure, "monolith structure" refers to a structure that exists in a separate phase in morphology, where particles are not agglomerated together. A particle structure opposite to a monolithic structure may include a structure in which relatively large-sized particle shapes (secondary particles) are formed by physical and / or chemical agglomeration of relatively small-sized particles (primary particles).
[0076] When lithium iron phosphate has a monolithic structure consisting of primary particles, the lithium iron phosphate particles are less likely to break during the rolling process compared to secondary particles, and therefore, the capacity reduction caused by the dissociation of the broken particles is smaller. In addition, when lithium iron phosphate is a primary particle with a monolithic structure, the migration of the binder can be reduced during the drying process of the positive electrode slurry, which will also be advantageous in terms of the interfacial adhesion between the positive electrode collector and the positive electrode active material layer.
[0077] The lithium iron phosphate may include a carbon coating on its surface. When the carbon coating is formed on the surface of the lithium iron phosphate, the conductivity may be increased, which may improve the resistance characteristics of the positive electrode.
[0078] The carbon coating layer can be formed using one or more raw materials selected from the group consisting of glucose, sucrose, lactose, starch, oligosaccharides, polysaccharides, fructose, cellulose, furfuryl alcohol polymers, block copolymers of ethylene and ethylene oxide, vinyl resins, cellulose-based resins, phenol-based resins, asphalt-based resins, and tar-based resins. Specifically, the carbon coating layer can be formed by mixing the raw materials with lithium transition metal phosphate and then performing a heat treatment process.
[0079] Average particle size D of lithium transition metal phosphate50 It may be 0.5 μm to 20.0 μm, preferably 0.5 μm to 10.0 μm, and more preferably 0.6 μm to 3.0 μm, more preferably 0.6 μm to 2.5 μm, and most preferably 0.7 μm to 1.5 μm. When the average particle size D of the positive electrode active material is 50 When the above range is satisfied, the mobility of lithium in the lithium transition metal phosphate is increased, so that the charge and discharge characteristics of the battery can be improved.
[0080] The BET surface area of lithium transition metal phosphates can be 5 m 2 / g to 20m 2 / g, especially 7m 2 / g to 18m 2 / g, and more particularly 9m 2 / g to 16m 2 / g. The above range is lower than that of conventional lithium iron phosphate. When the above range is satisfied, even in a positive electrode slurry composition having a relatively small amount of dispersant, agglomeration of lithium transition metal phosphate can be effectively suppressed.
[0081] The positive electrode according to one embodiment of the present invention may include particles having different average particle sizes (D 50 ) range of the first lithium iron phosphate and the second lithium iron phosphate. Specifically, the lithium iron phosphate included in the first positive electrode active material layer may include an average particle size D 50 The first lithium iron phosphate has an average particle size D of 0.5 μm to 2 μm. 50 The second lithium iron phosphate has a thickness of 3.5 μm to 15 μm.
[0082] The binder contained in the positive electrode active material layer, especially the fluorine-based binder, tends to adhere to the lithium iron phosphate rather than to the positive electrode current collector at the interface between the positive electrode current collector and the positive electrode active material layer, and this phenomenon can increase with the increase of the specific surface area of the lithium iron phosphate particles. Therefore, if the first positive electrode active material layer interfacing with the positive electrode current collector includes a large average particle size D 50 And thus, the second lithium iron phosphate having a smaller specific surface area, the total specific surface area of the lithium iron phosphate to which the binder can be bonded is reduced, and the interface adhesion between the current collector and the positive electrode active material layer can be significantly improved.
[0083] In one embodiment, the average particle size D of the first lithium iron phosphate 50 The average particle size D of the second lithium iron phosphate may be 0.5 μm to 2 μm, preferably 0.55 μm to 1.8 μm, and more preferably 0.6 μm to 1.6 μm. 50 The thickness may be 3.5 μm to 15 μm, preferably 3.8 μm to 12 μm, and more preferably 4 μm to 10 μm.
[0084] In one embodiment, the weight ratio of the first lithium iron phosphate to the second lithium iron phosphate may be 50:50 to 99.9:0.1, preferably 55:45 to 95:1, and more preferably 6:4 to 9:1. When the weight ratio of the first lithium iron phosphate to the second lithium iron phosphate satisfies the above range, the effect of improving adhesion is excellent, and the electrical properties of the positive electrode are excellent. If there is too much secondary lithium iron phosphate having a relatively large average particle size, the viscosity of the positive electrode slurry may increase significantly, and the rolling performance of the positive electrode may deteriorate, which is not preferred.
[0085] The first lithium iron phosphate may be a primary particle, and the second lithium iron phosphate may be a primary particle or a secondary particle.
[0086] When the first positive electrode active material layer includes the first lithium iron phosphate and the second lithium iron phosphate, the average particle size (D 50 ) can be 0.5 μm to 20.0 μm; 0.5 μm to 10.0 μm; 0.5 μm to 2 μm; 0.55 μm to 1.8 μm; 0.6 μm to 3.0 μm; 0.6 μm to 2.5 μm; 0.6 μm to 1.6 μm; 0.7 μm to 1.5 μm. The second positive electrode active material layer is used to improve the flexibility of the positive electrode, wherein the lithium iron phosphate included in the second positive electrode active material layer has a smaller average particle size, which is preferred in terms of the flexibility of the positive electrode.
[0087] The lithium iron phosphate of the present invention may be included in the first positive electrode active material layer and the second positive electrode active material layer in equal amounts or different amounts. In a specific example, based on the total weight of the first positive electrode active material layer, the lithium iron phosphate may be included in the first positive electrode active material layer in an amount of 93.5% to 98% by weight, more specifically 94% to 97.5% by weight, and more specifically 94.5% to 97% by weight. In addition, based on the total weight of the second positive electrode active material layer, the lithium iron phosphate may be included in the second positive electrode active material layer in an amount of 94% to 99% by weight, more specifically 94.5% to 98.5% by weight, and more specifically 95% to 98% by weight. When the content of lithium iron phosphate meets the above range, the battery capacity of the positive electrode can be improved by ensuring sufficient positive electrode energy density.
[0088] (2) Adhesive
[0089] The first positive electrode active material layer and the second positive electrode active material layer including the positive electrode according to the present invention each include both a fluorine-based binder and a rubber-based binder as a binder.
[0090] The fluorine-based adhesive may be a polyvinylidene fluoride (PVDF)-based polymer including vinylidene fluoride (VDF) as a monomer. Specific examples of PVDF-based polymers may include PVDF homopolymers, PVDF-HFP (Poly (vinylidenefluoride-co-hexafluoropropylene), poly (vinylidene fluoride-co-hexafluoropropylene)), PVDF-CTFE (Poly (vinylidene fluoride-co-chloro trifluoroethylene), poly (vinylidene fluoride-chlorotrifluoroethylene), PVDF-TFE (Poly (vinylidene tetrafluoroethylene), polyvinylidene tetrafluoroethylene), PVDF-TrFE (Poly (vinylidene trifluoroethylene), polyvinylidene trifluoroethylene), and the like.
[0091] The fluorine-based binder, together with the rubber-based binder, imparts adhesion between the positive electrode active material and the conductive material and adhesion between the current collector and the positive electrode active material layer.
[0092] The weight average molecular weight (Mw) of the fluorine-based binder may be 300,000 to 2,000,000, preferably 400,000 to 1,500,000, and most preferably 500,000 to 1,300,000. When the weight average molecular weight of the fluorine-based binder satisfies the above numerical range, the viscosity of the positive electrode slurry is easily within the desired range, and the positive electrode adhesion can be maximized with a lower content range.
[0093] The fluorine-based binder included in each of the first positive active material layer and the second positive active material layer may be the same compound, have the same weight average molecular weight, and the same chemical formula.
[0094] In the positive electrode according to the exemplary embodiment of the present invention, the content (weight %) of the fluorine-based binder contained in the first positive electrode active material layer of the lower layer is equal to or greater than the content (weight %) of the fluorine-based binder contained in the second positive electrode active material layer of the upper layer, so that the ratio (P2 / P1) of the weight P2 of fluorine contained in the second positive electrode active material layer to the weight P1 of fluorine contained in the first positive electrode active material layer is 1 or less, more preferably 0.5 to 1, preferably 0.52 to 0.95, and more preferably 0.53 to 0.85. If the ratio (P2 / P1) of P2 to P1 is greater than 1, it is undesirable in terms of adhesion.
[0095] The weight P1 of fluorine contained in the first positive electrode active material layer and the weight P2 of fluorine contained in the second positive electrode active material satisfying the above ratio range are due to the difference in the content of the fluorine-based binder contained in the first positive electrode active material layer and the second positive electrode active material layer, respectively.
[0096] In other words, the fluorine-based adhesive contains fluorine element, while the lithium iron phosphate, rubber-based adhesive, rubber-based dispersant and conductive material comprising the positive electrode of the present invention do not contain fluorine element, so that the weight of fluorine contained in the first positive electrode active material layer and the second positive electrode active material layer is proportional to the content (weight) of the fluorine-based adhesive contained in the first positive electrode active material layer and the second positive electrode active material layer, respectively.
[0097] Fluorine-based adhesives have the advantage of exhibiting excellent adhesion, but because fluorine-based adhesives have a crystalline structure, they are less flexible than rubber-based adhesives. Therefore, increasing the content of the fluorine-based adhesive having excellent adhesion in the first positive active material layer interfacing with the positive electrode collector and reducing the content of the fluorine-based binder in the second positive active material that requires flexibility has the effect of improving the interfacial adhesion of the positive electrode and preventing the electrode from being desorbed from the surface of the electrode in the event of an external impact. Therefore, by controlling the content of the fluorine-based adhesive in the first positive active material layer and the second positive active material layer as described above, the positive electrode according to the present invention having the same adhesive content has better adhesion than the positive electrode consisting of a single layer.
[0098] In an exemplary embodiment, the content of the fluorine-based binder in the first positive electrode active material layer may be 1.5 wt % to 3.0 wt %, preferably 1.6 wt % to 2.7 wt %, more preferably 1.7 wt % to 2.5 wt %. In addition, the content of the fluorine-based binder in the second positive electrode active material layer may be 0.8 wt % to 2.4 wt %, preferably 1.0 wt % to 2.2 wt %, more preferably 1.2 wt % to 2.0 wt %.
[0099] In addition, the content of the fluorine-based binder in the total positive electrode active material layer including the first positive electrode active material layer and the second positive electrode active material layer may be 1.2 wt % to 2.6 wt %, preferably 1.4 wt % to 2.4 wt %, and more preferably 1.6 wt % to 2.2 wt %.
[0100] At the same time, the rubber-based binder improves the flexibility of the positive electrode, increases the loading capacity of the positive electrode and improves the rolling performance. In addition, the improved flexibility inhibits the desorption of part of the positive electrode active layer under external physical impact, thereby providing an electrode with excellent capacity.
[0101] According to an exemplary embodiment of the present invention, the rubber-based adhesive may be hydrogenated nitrile rubber (HNBR). Hydrogenated nitrile rubber (HNBR) refers to nitrile rubber (NBR) that has been hydrogenated so that double bonds originally contained in the nitrile rubber (NBR) become single bonds.
[0102] The hydrogenated nitrile rubber may have a repeating unit content derived from acrylonitrile (AN) of 20 to 50 wt %, more preferably 25 to 45 wt %, and most preferably 30 to 40 wt %, based on the total weight.
[0103] The inventors of the present invention have found that a hydrogenated nitrile rubber (HNBR) having a weight average molecular weight (Mw) of 130,000 g / mol or more significantly improves the brittleness of the positive electrode including lithium iron phosphate as a positive electrode active material. The weight average molecular weight (Mw) of hydrogenated nitrile rubber can be 130,000 g / mol or more, preferably 150,000 g / mol to 1,000,000 g / mol, more preferably 200,000 g / mol to 500,000 g / mol. When the weight average molecular weight (Mw) of hydrogenated nitrile rubber is within the above range, due to the improvement of the flexibility of the positive electrode active material layer, the rolling density of the positive electrode can be increased, and the increased rolling density can have the effect of reducing the positive electrode resistance.
[0104] The rubber-based binder included in each of the first positive active material layer and the second positive active material layer may be the same compound, and may have the same weight average molecular weight and the same chemical formula.
[0105] Meanwhile, the rubber-based binder included in each of the first positive electrode active material layer and the second positive electrode active material layer may satisfy the following Condition 1. The following value of R2 / R1 may preferably be 1 to 2.9, more preferably 1.1 to 2.8.
[0106] [Condition 1].
[0107] 1≤R2 / R1≤3
[0108] R1 represents the content (wt%) of the rubber-based binder in the first positive electrode active material layer,
[0109] R2 represents the content (wt%) of the rubber-based binder in the second positive electrode active material layer.
[0110] A value of R2 / R1 greater than 3 is undesirable because it may result in an excessive amount of rubber-based binder in the second positive active material layer, which may increase the viscosity of the slurry used for the second positive active material layer, resulting in poor coating performance. Conversely, a value less than 1 is undesirable because it may result in a low amount of rubber-based binder in the second positive active material layer, resulting in poor overall positive electrode flexibility.
[0111] In an exemplary embodiment, the content of the rubber-based binder in the first positive electrode active material layer may be 0.2 wt % to 0.9 wt %, preferably 0.3 wt % to 0.8 wt %, more preferably 0.4 wt % to 0.7 wt %. The content of the rubber-based binder in the second positive electrode active material layer may be 0.3 wt % to 1.0 wt %, preferably 0.4 wt % to 0.9 wt %, more preferably 0.5 wt % to 0.8 wt %. In addition, the content of the rubber-based binder in the total amount of the first positive electrode active material layer and the second positive electrode active material layer may be 0.25 wt % to 0.85 wt %, preferably 0.35 wt % to 0.75 wt %, more preferably 0.4 wt % to 0.65 wt %.
[0112] When the content of the rubber-based binder included in each of the first positive electrode active material layer and the second positive electrode active material layer reaches the above degree, the positive electrode flexibility is improved and the coating stability of the slurry is also improved, so that each of the first positive electrode active material layer and the second positive electrode active material layer can be uniformly coated.
[0113] In the first positive active material layer, the weight ratio of the fluorine-based binder to the rubber-based binder may be 90: 10 to 75: 25, preferably 8: 1 to 4: 1, and more preferably 7: 1 to 1: 1. When the weight ratio of the fluorine-based binder to the rubber-based binder satisfies the above range, the coating stability of the slurry may be excellent, and the interface adhesion between the positive current collector and the first positive active material layer may be excellent.
[0114] In the second positive electrode active material layer, the weight ratio of the fluorine-based binder to the rubber-based binder may be 80:20 to 60:40, preferably 75:25 to 60:40. When the weight ratio of the fluorine-based binder to the rubber-based binder satisfies the above range, the coating stability of the slurry is excellent, and the flexibility of the positive electrode is excellent.
[0115] In addition, the total amount of the fluorine-based binder and the rubber-based binder included in each of the first positive active material layer and the second positive active material layer may be 1.8 wt % to 3.6 wt % based on the entire positive active material layer.
[0116] (3) Dispersant
[0117] The first positive electrode active material layer and the second positive electrode active material layer including the positive electrode according to the present invention each include a rubber-based dispersant.
[0118] The dispersant is used to increase the dispersibility of the components of the active material layer. In particular, the dispersant increases the dispersibility of the conductive material. The rubber-based dispersant of the present invention is also used to adjust the viscosity of the positive electrode slurry to a suitable range.
[0119] The rubber-based dispersant of the present invention may be hydrogenated nitrile rubber (HNBR). Hydrogenated nitrile rubber (HNBR) means that the double bonds contained in the original nitrile rubber (NBR) have been converted into single bonds through a hydrogenation reaction.
[0120] The weight average molecular weight (Mw) of hydrogenated nitrile rubber can be 10,000g / mol to 100,000g / mol, preferably 10,000g / mol to 80,000g / mol, more preferably 10,000g / mol to 50,000g / mol. When the weight average molecular weight of dispersant hydrogenated nitrile rubber meets the above range, the solvent wettability (wetting) and dispersibility of lithium iron phosphate particles can be improved, and the particle agglomeration of lithium iron phosphate can be suppressed. In addition, binder and lithium iron phosphate particles can be mixed very effectively, which also helps to improve the interface adhesion between positive electrode collector and the first positive electrode active material layer.
[0121] The hydrogenated nitrile rubber also improves the positive electrode conductive network by inhibiting the agglomeration of the electrode material, and even if the electrode material does agglomerate, it agglomerates in a spherical rather than linear manner, thereby minimizing the specific surface area of the agglomerated electrode material, compared to if the electrode material agglomerates linearly. As a result, the surface area of the positive electrode active material adjacent to the agglomerated electrode material that cannot participate in the lithium insertion / extraction reaction is minimized, thereby reducing the discharge resistance of the lithium secondary battery.
[0122] The content of the dispersant in the first positive electrode active material layer may be 0.01 wt % to 0.7 wt %, preferably 0.05 wt % to 0.6 wt %, more preferably 0.1 wt % to 0.5 wt %. The content of the dispersant in the second positive electrode active material layer may also be in the above range. When the content of the dispersant satisfies the above range, the agglomeration of the positive electrode active material can be suppressed, thereby preventing the gelation of the positive electrode slurry composition.
[0123] (4) Conductive materials
[0124] The first positive electrode active material layer and the second positive electrode active material layer included in the positive electrode according to the present invention each include a conductive material.
[0125] The conductive material is intended to improve the conductivity of the electrode, and is not particularly limited as long as it has conductivity without causing chemical changes in the battery, for example, graphite; carbon black, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, summer black, etc.; conductive fiber, such as carbon fiber or metal fiber; metal powder, such as carbon fluoride powder, aluminum powder, nickel powder; conductive whisker, such as zinc oxide, potassium titanate; conductive metal oxide, such as titanium oxide; conductive material, such as polyphenyl derivatives; and the like. Among these conductive materials, carbon nanotubes, carbon nanofibers and carbon black are preferred as the conductive material of the present invention, wherein carbon nanotubes are most preferred. The conductive network of carbon nanotubes is most preferred as the conductive material included in the positive electrode of the present invention because it can alleviate the phenomenon of binder lifting during the drying process of the positive electrode slurry.
[0126] Carbon nanotubes are graphite sheets with a nanometer-scale diameter cylindrical shape and sp2 bond structure, which exhibit the characteristics of a conductor or semiconductor depending on the angle and structure of the graphite sheet bending. Depending on the number of bonds forming the wall, carbon nanotubes can be classified into single-walled carbon nanotubes (SWCNT, Single-walled carbon nanotube), multi-walled carbon nanotubes (multi-walled carbon nanotube), or multi-walled carbon nanotubes, and these carbon nanotubes can be selected according to the purpose of the dispersion.
[0127] The carbon nanotube may also have a secondary shape formed by agglomeration or arrangement of a plurality of carbon nanotubes, for example, a bundle type carbon nanotube in the form of a bundle or rope in which a plurality of carbon nanotubes are arranged or aligned side by side in a specific direction, or an entangled type carbon nanotube in the form of a ball or potato in which a plurality of carbon nanotubes are intertwined without a specific direction. In terms of dispersibility, the carbon nanotube is preferably a bundled carbon nanotube.
[0128] The BET specific surface area of carbon nanotubes can be 100 m 2 / g to 1000m 2 / g, 150m 2 / g to 800m 2 / g, 150m 2 / g to 500m 2 / g, 150m 2 / g to 300m 2 / g, or 150m 2 / g to 200m 2 / g.
[0129] When the conductive material is carbon nanotubes, the content of the conductive material in each of the first positive electrode active material layer and the second positive electrode active material layer may be 0.3 wt % to 2.0 wt %, 0.6 wt % to 1.5 wt %, and more particularly 0.7 wt % to 1.3 wt %. If the content of the conductive material is less than 0.3 wt %, the binder lifting phenomenon may further increase during electrode drying, which is undesirable, and if the content of the conductive material is greater than 2.0 wt %, the content of the dispersant may increase together with the content of the positive electrode active material, which is also undesirable.
[0130] The conductive material included in the first positive electrode active material layer and the second positive electrode active material layer may be the same content or different contents. If the contents of the conductive material included in the first positive electrode active material layer and the second positive electrode active material layer are different, the following condition 2 may be satisfied.
[0131] [Condition 2]
[0132] 0.5≤E2 / E1≤0.9
[0133] E1 represents the linear conductive material content in the first active material layer (wt%),
[0134] E2 represents the linear conductive material content (wt %) in the second active material layer.
[0135] In the positive electrode satisfying the above condition 2, the content of the conductive material in the first positive electrode active layer intersecting with the positive electrode collector is greater than the content of the conductive material in the second positive electrode active layer, so that the conductive network is well formed by the conductive material in the first positive electrode active layer, and the conductive network suppresses the binder migration phenomenon, thereby improving the interface adhesion between the positive electrode collector and the first positive electrode active layer. And the improved interface adhesion can suppress the volume change during charging and discharging, thereby reducing the interface resistance of the positive electrode, thereby improving the resistance characteristics of the positive electrode.
[0136] If condition 2 is satisfied, the content of the conductive material in the first positive electrode active material layer may be 1.0 wt % to 1.5 wt %, preferably 1.1 wt % to 1.4 wt %. In addition, the content of the conductive material in the second positive electrode active material layer may be 0.4 wt % to 0.95 wt %, preferably 0.6 wt % to 0.90 wt %.
[0137] The positive electrode according to the present invention can be manufactured according to a conventional method for manufacturing a positive electrode. Specifically, a positive electrode slurry composition including a positive electrode active material, a conductive material, a binder and a dispersant can be prepared, the positive electrode slurry composition is applied to a positive electrode collector, and then dried and rolled to prepare the positive electrode.
[0138] In another method, the positive electrode can also be prepared by casting the positive electrode slurry composition onto a separate support and then laminating a film obtained by peeling off the support onto a positive electrode current collector.
[0139] According to one embodiment of the present invention, the positive electrode may have a porosity in the range of 26% to 34%, preferably in the range of 26.5% to 33%, and more preferably in the range of 27% to 30%, calculated by the following formula 1. When the porosity of the positive electrode satisfies the above range, both the flexibility and resistance properties of the positive electrode may be excellent.
[0140] [Formula 1]
[0141] Porosity = {1-(measured density of positive electrode active material layer / true density of positive electrode active material)}×100
[0142] Porosity refers to the porosity of the positive electrode active material layer including both the first positive electrode active material layer and the second positive electrode active material layer. In Formula 1, the "measured density of the positive electrode active layer" is the density calculated by measuring the weight and volume of the positive electrode active layer separated from the positive electrode current collector of the wound positive electrode, and the "true density of the positive electrode active material" is the density of the positive electrode active material particles themselves excluding the volume of the pores, which can be measured using a densitometer Pycnometer (AccuPycII 1340).
[0143] During the manufacturing process of the positive electrode, the porosity can be adjusted to the above numerical range by appropriately adjusting the thickness change rate of the positive electrode active material layer before and after rolling during the rolling process. Specifically, the greater the thickness change rate before and after rolling, the smaller the porosity can be, and conversely, the smaller the thickness change rate before and after rolling, the greater the porosity of the positive electrode active material layer. The thickness change rate can be calculated as follows.
[0144] Thickness change rate = (thickness of positive electrode active material before rolling - thickness of positive electrode active material after rolling) / thickness of positive electrode active material before rolling
[0145] The thickness variation rate can be controlled by the preload applied to the positive electrode during rolling of the positive electrode, that is, the larger the preload, the larger the thickness variation rate before and after rolling, and the smaller the preload, the smaller the thickness variation rate before and after rolling.
[0146] Since the positive electrode according to one embodiment of the present invention includes the first positive active material layer maximizing adhesion and the second positive active material layer maximizing flexibility, positive electrode adhesion and flexibility can be achieved with less binder content than a conventional single-layer positive electrode.
[0147] As a result, a high-load positive electrode can be manufactured, the battery resistance of the secondary battery can be reduced by preventing the positive electrode from being dissociated, the capacity and output characteristics of the battery can be improved, and defects in the manufacturing process can be reduced.
[0148] The positive electrode of the present invention may have an adhesion between the positive electrode current collector and the positive electrode active material layer of at least 20 gf / 20 mm, more specifically at least 25 gf / 20 mm, as measured by a 90° peeling test.
[0149] Furthermore, the positive electrode of the present invention may have such flexibility that, in a flexibility test in which the positive electrode is lifted after contacting a phi measuring rod on the positive electrode active material layer, the maximum value of the measuring rod at which cracks are generated is Value is or smaller, more specifically or smaller, and even more particularly for or smaller.
[0150] Lithium secondary battery
[0151] Next, a lithium secondary battery according to the present invention will be described.
[0152] A lithium secondary battery according to one embodiment of the present disclosure may include a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte.
[0153] In a lithium secondary battery, the positive electrode is the same as the positive electrode described above. For example, the positive electrode includes: a positive electrode current collector; a first positive electrode active material layer formed on one or both sides of the positive electrode current collector; and a second positive electrode active material layer formed on the first positive electrode active material layer; wherein the first positive electrode active material layer and the second positive electrode active material layer each include lithium iron phosphate, a coating material, a fluorine-based adhesive, a rubber-based adhesive, and a rubber-based dispersant, and the weight P2 of fluorine contained in the second positive electrode active material layer and the weight P1 of fluorine contained in the first positive electrode active material layer (P2 / P1) is 1 or less, wherein the weight (A) of the first positive electrode active material layer is in the range of 17% to 99% of the total weight (A+B) of the first positive electrode active material layer and the second positive electrode active material layer.
[0154] The rubber-based adhesive may be hydrogenated nitrile rubber (HNBR) having a weight average molecular weight (Mw) of 130,000 g / mol or more.
[0155] The rubber-based dispersant may be hydrogenated nitrile rubber (HNBR) having a weight average molecular weight (Mw) in the range of 10,000 g / mol to 100,000 g / mol.
[0156] The rubber-based binder included in each of the first positive electrode active material layer and the second positive electrode active material layer may satisfy the following Condition 1.
[0157] [Condition 1].
[0158] 1≤R2 / R1≤3
[0159] R1 represents the content (wt%) of the rubber-based binder in the first positive electrode active material layer,
[0160] R2 represents the content (wt%) of the rubber-based binder in the second positive electrode active material layer.
[0161] The lithium iron phosphate, the fluorine-based binder, the rubber-based binder, and the rubber-based dispersant included in the first positive electrode active material layer and the second positive electrode active material layer have been previously described in detail, and a repeated description will be omitted.
[0162] For example, the negative electrode may be prepared by preparing a negative electrode forming composition including a negative electrode active material, a negative electrode binder, and a negative electrode conductive material on a negative electrode collector, and then applying the composition to the negative electrode collector.
[0163] The negative electrode active material is not particularly limited, and any compound capable of reversibly inserting and extracting lithium can be used. Specific examples thereof include: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, amorphous carbon, high crystallinity carbon, and the like; metal compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, Al alloys, and the like; and composite materials including metal compounds and carbonaceous materials. In addition, examples of low crystallinity carbon include soft carbon and hard carbon, and examples of high crystallinity carbon include natural graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesophase-carbon microbeads, mesophase pitches, and high temperature sintered carbon such as petroleum or coal tar pitch derived cokes, which can be used alone or in mixtures of two or more thereof. In addition, as a negative electrode active material, a lithium metal film can be used.
[0164] The negative electrode conductive material is used to impart conductivity to the electrode, and any conductive material that does not cause chemical changes in the battery and has conductivity can be used without particular limitation. Specific examples of negative electrode conductive materials include graphite, such as natural graphite, artificial graphite, and the like; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, carbon nanotubes, and the like; powders or fibers of metals such as copper, nickel, aluminum, silver, and the like; conductive whiskers, such as zinc oxide, potassium titanate, and the like; conductive metal oxides, such as titanium oxide and the like; and conductive polymers, such as polyphenylene derivatives and the like, which can be used alone or in mixtures of two or more thereof. The content of the negative electrode conductive material can generally be 1% to 30% by weight, particularly 1% to 20% by weight, and more particularly 1% to 10% by weight, relative to the total weight of the negative electrode active material layer.
[0165] The negative electrode binder is used to enhance the adhesion between the negative electrode active material particles and the adhesion between the negative electrode active material and the negative electrode collector. Specific examples of negative electrode binders include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, which can be used alone or in mixtures of two or more thereof. The content of the negative electrode binder can generally be 1% to 30% by weight relative to the total weight of the negative electrode active material layer, particularly 1% to 20% by weight, and more particularly 1% to 10% by weight.
[0166] Meanwhile, the negative electrode current collector is not particularly limited as long as it does not cause chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, or copper or stainless steel, aluminum-cadmium alloy, or the like whose surface has been treated with carbon, nickel, titanium, silver, etc., can be used as the negative electrode current collector.
[0167] In addition, the negative electrode current collector may have a thickness of 3 μm to 500 μm, and, like the positive electrode current collector, fine irregularities may be formed on the surface of the negative electrode current collector to increase the binding force of the negative electrode active material. For example, the negative electrode current collector may be used in various forms including films, sheets, foils, nets, porous bodies, foams, nonwoven fabrics, and the like.
[0168] At the same time, as a separator in a lithium secondary battery, any separator commonly used as a separator in a lithium secondary battery can be used without particular restriction, and in particular, it is preferred to show low resistance to the migration of electrolyte ions and have an excellent electrolyte impregnation ability. Specifically, a porous polymer film can be used, for example, a porous polymer film formed by a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a stacked structure with more than two layers thereof. In addition, a typical porous nonwoven fabric can be used, for example, a nonwoven fabric formed by a high melting point glass fiber or a polyethylene terephthalate fiber. In addition, the separator can be a porous film having a pore size of 0.01 μm to 10 μm and a thickness of 5 μm to 300 μm.
[0169] Meanwhile, in the lithium secondary battery, the electrolyte may include an organic solvent and a lithium salt generally used in an electrolyte, and they are not particularly limited.
[0170] As the organic solvent, any solvent that can be used as a medium through which ions participating in the electrochemical reaction of the battery can migrate can be used without particular limitation. Specifically, as the organic solvent, an ester-based solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, or the like; an ether-based solvent such as dibutyl ether, tetrahydrofuran, or the like; a ketone-based solvent such as cyclohexanone or the like; an aromatic hydrocarbon-based solvent such as benzene, fluorobenzene, or the like; or a carbonate-based solvent such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), or the like can be used.
[0171] Among these materials, carbonate-based solvents are preferably used, and more preferably a mixture of a cyclic carbonate having high ionic conductivity and high dielectric constant such as ethylene carbonate or propylene carbonate and a linear carbonate-based compound having low viscosity (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, or the like) which can improve the charging and discharging performance of the battery.
[0172] The lithium salt is not particularly limited as long as it is a compound that can provide the lithium ions used in the lithium secondary battery. Specifically, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2 or the like can be used as the lithium salt. The lithium salt is preferably included in the electrolyte at a concentration of about 0.6 mol% to 2 mol%.
[0173] In addition to the above electrolyte components, the electrolyte may further include, for example, one or more additives such as pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, N-glyme, hexanetriamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum chloride, for the purpose of improving the life characteristics of the battery, suppressing the reduction of the battery capacity, improving the discharge capacity of the battery, etc. The additive may be included in an amount of 0.1 wt % to 5 wt % based on the total weight of the electrolyte.
[0174] The lithium secondary battery according to the present disclosure can be manufactured by inserting a separator between a positive electrode and a negative electrode to form an electrode assembly, placing the electrode assembly in a cylindrical battery case or a prismatic battery case, and injecting an electrolyte. Alternatively, the lithium secondary battery can be manufactured by stacking electrode assemblies, impregnating the electrode assemblies with electrolyte, placing the resultant in a battery case, and sealing the battery case.
[0175] In the manufacture of a lithium secondary battery according to the present disclosure, the electrode assembly may be dried to remove one or more organic solvents selected from the group consisting of N-methyl-2-pyrrolidone (NMP), acetone, ethanol, propylene carbonate, ethyl methyl carbonate, ethylene carbonate, and dimethyl carbonate used in the manufacture of the positive electrode. When an electrolyte having the same components as the organic solvent used in the manufacture of the positive electrode is used as the electrolyte, the process of drying the electrode assembly may be omitted.
[0176] Unlike the above-described lithium secondary battery, a lithium secondary battery according to another embodiment of the present disclosure may be an all-solid-state battery.
[0177] As the battery case, any battery case commonly used in the art can be used, and there is no limitation on the shape according to the use of the battery. For example, the shape of the battery case can be cylindrical, prismatic, pouch, coin, or the like using a can.
[0178] The lithium secondary battery according to the present disclosure can be used in the fields of portable devices such as mobile phones, notebook computers, digital cameras, and the like, energy storage systems (ESS), and electric vehicles such as hybrid electric vehicles (HEV) and the like because it stably exhibits excellent discharge capacity, output characteristics, and capacity retention rate.
[0179] Hereinafter, the present disclosure will be described in more detail with reference to Examples. However, the following Examples are presented only to illustrate the present disclosure, and the scope of the present disclosure is not limited to the following Examples.
[0180] Example 1: Preparation of positive electrode
[0181] (1) Preparation of the first positive electrode slurry
[0182] Preparation of carbon nanotubes (CNT, BET specific surface area; 250 m 2 / g) and a dispersion of a hydrogenated nitrile rubber having a weight average molecular weight (Mw) of 30,000 g / mol as a rubber-based dispersant.
[0183] The average particle size D of the primary particles having a monolithic structure is 50 Lithium iron phosphate LiFePO4 of 1.1 μm, polyvinylidene fluoride (PVdF) with a weight average molecular weight (Mw) of 1,000,000 g / mol as a fluorine-based binder, hydrogenated nitrile rubber with a weight average molecular weight (Mw) of 310,000 g / mol as a rubber-based binder, and a dispersant were added to N-methylpyrrolidone (NMP) solvent, and then mixed at 2500 rpm for 90 minutes using a homogenizer to prepare a first positive electrode slurry. In the first positive electrode slurry, lithium iron phosphate, conductive material, fluorine-based binder, rubber-based binder and dispersant are present in a weight ratio of 96:1.0:2.2:0.5:0.3. In addition, the solids in the first positive electrode slurry are 62% by weight.
[0184] (2) Preparation of the Second Positive Electrode Slurry
[0185] The second positive electrode slurry was prepared in the same manner as the first positive electrode slurry, except that the weight ratio of lithium iron phosphate, conductive material, fluorine-based binder, rubber-based binder and dispersant in the positive electrode slurry was changed to 96.8:1.0:1.4:0.5:0.3. The solid in the second positive electrode slurry was 67% by weight.
[0186] (3) Manufacturing of the Second Positive Electrode
[0187] Using a double slot die coater, the coating load on aluminum foil was 450 mg / 25 cm 2 The first cathode slurry and the loading amount are 150mg / 25cm 2 The second positive electrode slurry is coated in such a manner that the second positive electrode slurry is laminated on the first positive electrode slurry.
[0188] Then, the positive electrode slurry was hot-air dried at 130° C. for 5 minutes to make the solid content of the positive electrode slurry greater than 99.0 wt %. Then, the positive electrode was prepared by rolling the positive electrode active material layer to have a porosity of 29%. The porosity refers to the porosity calculated by the following formula 1.
[0189] [Formula 1]
[0190] Porosity = {1-(measured density of positive electrode active material layer / true density of positive electrode active material)}×100
[0191] Example 2: Preparation of positive electrode
[0192] The positive electrode was manufactured in the same manner as in Example 1, except that the coating loading was 300 mg / 25 cm 2 The first positive electrode slurry and coating loading is 300 mg / 25 cm 2 Second positive electrode slurry.
[0193] Example 3: Preparation of positive electrode
[0194] The positive electrode was manufactured in the same manner as in Example 1, except that the coating loading was 150 mg / 25 cm 2 The first cathode slurry and coating loading is 450 mg / 25 cm 2 Second positive electrode slurry.
[0195] Example 4: Preparation of positive electrode
[0196] The first positive electrode was manufactured according to Example 1, except that the first lithium iron phosphate LiFePO4 (average particle size D 50 The primary particles are 1.1 μm and have a monolithic structure) and the second lithium iron phosphate LiFePO4 (average particle size D50 The second positive electrode is coated with a secondary particle with a loading of 300 mg / 25 cm 2 The first cathode slurry and the loading amount are 300mg / 25cm 2 The second positive electrode slurry.
[0197] Example 5: Preparation of positive electrode
[0198] The first positive electrode was manufactured according to Example 1, except that the first lithium iron phosphate LiFePO4 (average particle size D 50 The primary particles are 1.1 μm and have a monolithic structure) and the second lithium iron phosphate LiFePO4 (average particle size D 50 The second positive electrode is coated with a secondary particle with a loading of 300 mg / 25 cm 2 The first cathode slurry and the loading amount are 300mg / 25cm 2 The second positive electrode slurry.
[0199] Example 6 to Example 7: Production of positive electrode
[0200] In each of the first positive electrode slurry and the second positive electrode slurry, the weight ratio of lithium iron phosphate, the conductive material, the fluorine-based binder, the rubber-based binder, and the rubber-based dispersant was changed as shown in Table 1, and the positive electrode was prepared according to Example 1, except that the coating loading was 300 mg / 25 cm 2 The first positive electrode slurry and coating loading is 300 mg / 25 cm 2 Second positive electrode slurry.
[0201] Comparative Example 1: Preparation of positive electrode
[0202] The first positive electrode slurry prepared in Example 1 was used at 600 mg / 25 cm 2 The loading amount of coated aluminum foil.
[0203] Then, a positive electrode was prepared in the same manner as in Example 1.
[0204] Comparative Example 2: Preparation of positive electrode
[0205] The second positive electrode slurry prepared in Example 1 was used at 600 mg / 25 cm 2 The loading amount of coated aluminum foil.
[0206] Then, a positive electrode was prepared in the same manner as in Example 1.
[0207] Comparative Examples 3 and 4: Preparation of Positive Electrode
[0208] In each of the first positive electrode slurry and the second positive electrode slurry, the weight ratio of lithium iron phosphate, the conductive material, the fluorine-based binder, the rubber-based binder, and the rubber-based dispersant was changed as shown in Table 1, and a positive electrode was prepared in the same manner as in Example 1, except that the coating loading was 300 mg / 25 cm 2 The first positive electrode slurry and coating loading is 300 mg / 25 cm 2 Second positive electrode slurry.
[0209] Comparative Example 5: Preparation of positive electrode
[0210] The positive electrode was prepared according to Example 1, except that the coating loading was 60 mg / 25 cm 2 The first cathode slurry and coating loading is 5400 mg / 25 cm 2 Second positive electrode slurry.
[0211] [Table 1]
[0212]
[0213]
[0214] Experimental Example 1: Evaluation of Adhesion of Positive Electrode
[0215] Each of the positive electrodes manufactured in Examples 1 to 7 and Comparative Examples 1 to 5 was vacuum dried at 130° C. for 2 hours, and then the adhesion between the positive electrode active material layer and the positive electrode collector was measured. The results are shown in Table 2.
[0216] Specifically, each positive electrode manufactured in Example 1 to Example 7 and Comparative Example 1 to Comparative Example 5 was cut into a length of 150 mm and a width of 20 mm, and the positive electrode surface was attached to a slide glass having a length of 75 mm and a width of 25 mm in the length direction using a double-sided tape. That is, the slide glass was attached to an area corresponding to half of the length direction of the positive electrode. In addition, a roller was used to perform 10 frictions so that the double-sided tape was evenly attached, thereby preparing an evaluation sample.
[0217] Next, the slide glass portion of the evaluation sample is fixed to the sample stage of the Universal Testing Machine (UTM) (Product Name: LS5, Manufacturer: AMETEK), and the half of the positive electrode without the slide glass attached is connected to the load sensor of the UTM. While the load sensor is moved to 50mm at an angle of 90° and a speed of 100mm / min, the load applied to the load sensor is measured. In this case, the average value of the load measured in the segment of 20mm to 40mm during the driving segment is obtained. This procedure is repeated 5 times in total, and the average value is evaluated as the positive electrode adhesion (gf / 20mm) of each sample.
[0218] Experimental Example 2: Evaluation of the Flexibility of the Positive Electrode
[0219] After vacuum drying at a temperature of 130° C. for 2 hours, the flexibility of each of the positive electrodes prepared in Examples 1 to 7 and Comparative Examples 1 to 5 was measured. The results are shown in Table 2.
[0220] Specifically, the positive electrode prepared in each of the above Examples 1 to 7 and Comparative Examples 1 to 5 was cut into a width of 10 cm and a length of 30 cm, and a diameter of Then, fold each cut positive electrode in half with the positive collector side facing the measuring rod, and lift both ends of the positive electrode at a speed of 10 mm per minute. Continue to lift until the force measured on the UTM is 5N. Measure each phi and observe whether the electrode has cracks through an optical microscope. If there are no cracks, use a smaller phi for testing. The diameter of the measuring rod that produces the cracks accordingly Shown in Table 2.
[0221] Experimental Example 3: Measuring the weight of fluoride
[0222] In each positive electrode according to the embodiment and the comparative example, 100 mg of the sample was taken out from each of the first positive electrode active layer and the second positive electrode active layer by scraping the first positive electrode active layer each time, and then, the weight of fluorine contained in each sample was measured using the combustion reactor method, and the ratio (P2 / P1) of the weight P2 of fluorine contained in the second positive electrode active layer to the weight P1 of fluorine contained in the first positive electrode active layer was calculated. The results are shown in Table 2.
[0223] In order to determine the weight of fluoride contained in each sample, the gas generated by complete combustion of the sample of the first positive electrode active material layer and the sample of the second positive electrode active material layer under high pressure oxygen conditions (40atm) was captured in an absorbent solution. The gas capture absorbent solution is a 1L solution containing 2.52g NaHCO3 and 2.52g Na2CO3. When fluoride ions are absorbed or dissolved in the gas capture absorbent solution, the weight of fluoride in each sample is determined using ion chromatography. The ion chromatography column and analysis conditions are as follows.
[0224] Ion Chromatography: ICS-3000
[0225] Column: IonPac AS18 (4×50 mm)
[0226] Detector: Suppressed conductivity detector
[0227] SRS current: 76mA
[0228] Injection volume: 20 μL
[0229] The same test was repeated three times, and the average values are shown.
[0230] Table 2 shows the ratio (P2 / P1) of the weight P2 of fluorine contained in the second positive electrode active material layer to the weight P1 of fluorine contained in the first positive electrode active material layer based on the results of ion chromatography analysis.
[0231] [Table 2]
[0232]
[0233] The positive electrode according to Comparative Example 1 includes a single-layer positive electrode having a composition of the respective first positive electrode active material layer of each positive electrode of Examples 1 to 3 and does not include a second positive electrode active material layer, and shows much higher flexibility than the positive electrode according to the above embodiment. The positive electrode according to Comparative Example 2 includes a single-layer positive electrode having a composition of the respective second positive electrode active material layer of each positive electrode of Examples 1 to 3 and does not include a first positive electrode active material layer, and shows much better adhesion than the positive electrode according to the above embodiment.
[0234] It has been found that the positive electrode according to Comparative Example 3, in which the ratio (P2 / P1) of the weight P2 of fluorine contained in the second positive electrode active layer to the weight P1 of fluorine contained in the first positive electrode active layer exceeds 1, has lower adhesion than the positive electrode of each example.
[0235] It was found that the positive electrode according to Comparative Example 4, which did not include the rubber-based binder, had lower flexibility than each of the positive electrodes of the Examples.
[0236] By comparing the respective adhesions of the positive electrodes according to Examples 1 to 3 and Comparative Example 5, it has been found that the adhesion of the positive electrode according to Comparative Example 5 (wherein the weight (A) of the first positive electrode active material layer is 10% of the total weight (A+B) of the first positive electrode active material layer and the second positive electrode active material layer) is the lowest, while the adhesion of the positive electrode according to Example 1 (wherein the weight ratio of the first positive electrode active material layer is the largest, which is 75%) is the best. Therefore, in the present invention, it is preferred to increase the weight ratio of the first positive electrode active material layer to increase the adhesion, and the weight (A) of the first positive electrode active material layer seems to be more than 10% of the total weight (A+B) of the first positive electrode active material layer and the second positive electrode active material layer to ensure minimum adhesion.
[0237] Comparing the respective flexibility of the positive electrodes according to Examples 1 to 3 and Comparative Example 5, it can be seen that the smaller the ratio of the weight (A) of the first positive electrode active material layer to the total weight (A+B) of the first positive electrode active material layer and the second positive electrode active material layer, the more favorable the flexibility. However, considering that the difference in their flexibility is not large, it seems preferable that the weight (A) of the first positive electrode active material layer is 25% to 75% of the total weight (A+B) of the first positive electrode active material layer and the second positive electrode active material layer in order to ensure flexibility and adhesion at the same time.
[0238] On the other hand, the positive electrode according to Example 4 and Example 5 includes an average particle size D 50 The first lithium iron phosphate has an average particle size D of 1.1 μm. 50 The second lithium iron phosphate with a particle size of 7 μm as the positive electrode active material in the first positive electrode active material layer shows better adhesion than the positive electrode according to Example 2. Thus, it can be expected that if the particle size of the positive electrode active material in the first positive electrode active material layer facing the current collector is controlled to be bimodal, the effect of improving the adhesion between the positive electrode current collector and the active material layer is maximized.
[0239] While the present invention has been shown and described in connection with the particular embodiments, it will be apparent to those skilled in the art that modifications and variations are possible without departing from the spirit and scope of the invention as set forth in the appended claims.
[0240] Therefore, the technical scope of the present invention should not be limited to the contents described in the detailed description of the specification but should be defined by the scope of the claims.
Claims
1. A positive electrode, comprising: positive electrode current collector; a first positive electrode active material layer formed on one side or both sides of the positive electrode current collector; and a second positive electrode active material layer, the second positive electrode active material layer being formed on the first positive electrode active material layer; wherein the first positive electrode active layer and the second positive electrode active layer each include lithium iron phosphate, a coating material, a fluorine-based binder, a rubber-based binder, and a rubber-based dispersant, And the ratio (P2 / P1) of the weight P2 of fluorine contained in the second positive electrode active layer to the weight P1 of fluorine contained in the first positive electrode active layer is 1 or less, and the weight (A) of the first positive electrode active layer is in the range of 17% to 99% of the total weight (A+B) of the first positive electrode active layer and the second positive electrode active layer.
2. The positive electrode according to claim 1, The weight of the first positive electrode active material layer (A) is in the range of 20% to 85% of the combined weight of the first positive electrode active material layer and the second positive electrode active material layer (A+B).
3. The positive electrode according to claim 1, The rubber-based adhesive and the rubber-based dispersant are hydrogenated nitrile rubber (HNBR) respectively.
4. The positive electrode according to claim 3, The rubber-based adhesive is a hydrogenated nitrile rubber (HNBR) having a weight average molecular weight (Mw) of at least 130,000 g / mol.
5. The positive electrode according to claim 3, The rubber-based adhesive is a hydrogenated nitrile rubber (HNBR) having a weight average molecular weight (Mw) in the range of 150,000 g / mol to 1,000,000 g / mol.
6. The positive electrode according to claim 3, The rubber-based dispersant is a hydrogenated nitrile rubber (HNBR) having a weight average molecular weight (Mw) in the range of 10,000 g / mol to 100,000 g / mol.
7. The positive electrode according to claim 1, The lithium iron phosphate included in the first positive electrode active material layer has an average particle size D 50 The first lithium iron phosphate has an average particle size D of 0.5 μm to 2 μm. 50 The second lithium iron phosphate has a thickness of 3.5 μm to 15 μm.
8. The positive electrode according to claim 7, The weight ratio of the first lithium iron phosphate to the second lithium iron phosphate is 50:50 to 99.9:0.
1.
9. The positive electrode according to claim 7, The average particle size D of the lithium iron phosphate included in the second positive electrode active material layer is 50 0.6μm to 3.0μm.
10. The positive electrode according to claim 1, The lithium iron phosphate is a compound represented by the following Formula 1. [Formula 1]. Li 1+a Fe 1-x M x (PO 4-b )X b (In the above formula 1, M includes one or more elements selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, X includes one or more elements selected from the group consisting of F, S, and N, and a, b, and x are -0.5≤a≤0.5, 0≤b≤0.1, and 0≤x≤0.5, respectively).
11. The positive electrode according to claim 1, The fluorine-based adhesive is a polyvinylidene fluoride (PVdF)-based polymer adhesive.
12. The positive electrode according to claim 1, The fluorine-based binder is included in the first positive electrode active material layer in an amount of 1.5 wt % to 3.0 wt %.
13. The positive electrode according to claim 1, The fluorine-based binder is included in the second positive electrode active material layer in an amount of 0.8 wt % to 2.4 wt %.
14. The positive electrode according to claim 1, The rubber-based binder included in each of the first positive electrode active material layer and the second positive electrode active material layer satisfies the following condition 1. [Condition 1]. 1≤R2 / R1≤3 R1 represents the content (wt%) of the rubber-based binder in the first positive electrode active material layer, R2 represents the content (wt%) of the rubber-based binder in the second positive electrode active material layer.
15. The positive electrode according to claim 1, wherein the rubber-based adhesive is included in the first positive electrode active material layer in an amount of 0.2 wt % to 0.9 wt %, The second positive electrode active material layer is included in an amount of 0.3 wt % to 1.0 wt %.
16. The positive electrode according to claim 1, The conductive material is carbon nanotubes.
17. The positive electrode according to claim 1, wherein the conductive material is included in each of the first positive electrode active material layer and the second positive electrode active material layer in an amount of 0.3 wt % to 2.0 wt %. 18 . A lithium secondary battery comprising the positive electrode according to claim 1 .